Problems of human capital preservation and development under digitalization conditions: national and regional contexts (Economics and region, 2023)
The main reasons for the loss of human capital in Ukraine over the last decade are summarized. The conditions that affect the fulfillment of the mission of preserving human capital in different regions of Ukraine ‒ occupied, front-line and rear regions ‒ have been determined. It is well-founded that measures to preserve human capital should be planned taking into account the gender and age composition of the population of the region, the state of security in one or another territory, the economic conditions in which the population lives, the presence or absence of opportunities for employment and training, the availability of education and medical care, the general mood of residents and their intentions for the future. The problems of preservation and development of human capital under the conditions of digitalization are outlined. The role of digital literacy in the implementation of the task of human capital development has been established. Ways to expand the use of digitalization opportunities to fulfill the task of preserving and developing human capital in Ukraine in wartime are recommended.
Keywords: human capital; war; economic recovery; human capital development; human capital preservation; digitalization